Empowering Women in Green Energy Business: Bridging Economic, Social, and Environmental Gaps in Rural Communities - Friska Indria Nora Harahap; Mustofa Kamil; Jajat S Ardiwinata; Sardin; Jubaidah Hasibuan (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2026)
This research aims to investigate the role of women in initiating green energy businesses in Cibodas Village and the factors influencing their empowerment. Qualitative methods were used to gain an in-depth understanding of women's experiences, perceptions, and empowerment strategies in the context of green energy business. In-depth interviews, focus group discussions, and participant observation were conducted to collect data from village women involved in the initiative. The research results show that village women have an important role in identifying potential natural resources, planning, and managing green energy projects, and promoting environmental awareness at the local level. Supporting factors such as family support, access to training and resources, and supportive regulations play a crucial role in empowering women, while inhibiting factors such as limited access to capital and technology, gender stereotypes, and lack of market access are challenges that need to be overcome. This research provides valuable insights for the development of sustainable development policies and practices, and highlights the importance of strengthening the role of women in the transformation towards green energy and a sustainable economy Keywords: women's empowerment, green energy business, gender roles, sustainable development